ANALISIS DAYA SAING DAERAH KECAMATAN DI KABUPATEN INDRAGIRI HULU - Sugeng Riono; Djaimi Bakce; Ahmad Rifai (Fakultas Pertanian, Universitas Riau, 2014)
The description about the competitiveness of a sub-district region is crucial in order to formulate the region development planning of Indragiri Hulu Regency. Through this study, several descriptions about the region competitiveness typhology were gained and then classified into three categories consisted of low, medium, and high. This study aimed to analyze the typology of district region competitiveness in Indragiri Hulu Regency. Factor analysis and main component analysis, were the method used to determine the three aformentioned categories. The prominent aspect gained from the research was there were four sub-districts that having high level of competitiveness, Rengat, Seberida, Batang Cenaku and Pasir Penyu Sub-district. Furthermore, there were four sub-district that were included in the medium level, there were Lirik, Batang Gangsal, Sungai Lala, and Kuala Cenaku Sub-district. Meanwhile, other six sub-districts that having low level of competitiveness were West Rengat, Batang Peranap, Kelayang, Rakit Kulim, LubukBatu Jaya, and Peranap Sub-district. In terms of increasing the competitiveness of sub-district area in Indragiri Hulu Regency, from nine prominent aspects, there were three aspects considered as the main concern they are the development and improvement of transportation infrastructure and utility, the development and improvement of agricultural resource potency, as well as the development and improvement of the added value towards the agricultural products.Keywords : Regional Planning, Regional Competitiveness, Competitiveness Typhology